In situ investigations of the phase change behaviour of tungsten oxide nanostructures - Thummavichai, Kunyapat; Wang, Nannan; Xu, Fang; Rance, Graham; Xia, Yongde; Zhu, Yanqiu (Royal Society, 2018)
This study appraises the use of in-situ diffraction and spectroscopy techniques, complemented with ex-situ electron microscopy analyses, to investigate the geometry and phase change behaviour of bundled ultrathin W18O49 nanowires and WO3 nanoparticles. Our in-situ X-ray diffraction (XRD) results have shown that the phase transition of WO3 nanoparticles occurs in sequence as the temperature increases, from monoclinic (room temperature) → orthorhombic (350 ºC) → tetragonal (800 °C), akin to bulk WO3; however, W18O49 nanowires remain stable as the monoclinic phase up to 500 °C, after which complete oxidation to WO3 and transformation to the orthorhombic β-phase at 550 °C is observed. The in-situ Raman spectroscopy investigations have shown that as the temperature increases, the Raman peaks downshift toward lower wavenumbers in both structures, which can be attributed to the increased bond lengths in the lattice. We have also demonstrated that the Raman shift at 187.6 cm-1 can be used as a fingerprint band for the phase transition from the γ- to the β-phase of the WO3 nanoparticle. Furthermore, WO3 nanoparticles exhibit the γ- to β-phase conversion at 275 °C, which is about 75 °C lower than the relaxation temperature of 350 °C for the monoclinic γ-W18O49 nanowires. We propose that this fundamental phase transition understanding can offer important guidance for the design and development of WOx-based nanodevices by defining their allowed operating conditions.